Informal Leadership and Infrastructure Development: The Role of Tungku Tigo Sajarangan in the Batang Agam Hydropower Project (1965–1976) - Israr, Israr; Anatona, Anatona (Analisis Sejarah, 2026)
This study examines the patterns and forms of support provided by the informal leadership institution of Tungku Tigo Sajarangan in Koto Tangah, Akabiluru District, Lima Puluh Kota Regency, during the development of the Batang Agam Hydroelectric Power Plant (PLTA Batang Agam) in Indonesia’s New Order period. Using the historical research method, this article explores the strategies adopted by government authorities and project managers to engage informal leaders at the nagari level where the project was implemented. The findings show that persuasive and empathetic approaches toward local landowning communities significantly facilitated project implementation. Rather than generating resistance, the Batang Agam hydropower project received broad support and active participation from the local population, mediated through the authority of Tungku Tigo Sajarangan. This case offers valuable historical insights for addressing contemporary land acquisition conflicts through inclusive, culturally grounded, and participatory approaches.